(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
High pressure acid leaching (HPAL) is the primary method to extract nickel from limonitic laterite, where the objective to reach high nickel recovery is met by leaching under extreme temperatures (T>250°C) and pressures (p>4MPa) conditions. The extreme processing conditions enforce the design of expensive facilities with high maintenance costs. Purpose of this work was to explore the possibility for nickel dissolution under more moderate HPAL temperatures and pressures. This was achieved by pretreatment of ore by reductive roasting, the common practice for ammoniacal leaching in Caron process, but not in HPAL. For the calcine with reduction degree of 93.4%, the results showed that 88.2% of nickel could be selectively extracted at 100°C with an acid/ore ratio of 0.164, leaving less then 5.0g/L iron in the solution. Further increase of leaching temperature, and the ensuing dehydration, transformed goethite in the leaching residue to hematite. When the temperatures were as high as 180°C, the recovery of nickel increased to 95.2%, within one hour, depressing the residual soluble iron to below 1.0g/L (pO2= 1.0 MPa, acid/ore= 0.287).